2017
DOI: 10.1016/j.tem.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Gene Expression and Life Span Regulation

Abstract: Aging-related diseases show a marked sex bias. For example, women live longer than men yet have more Alzheimer’s disease and osteoporosis, whereas men have more cancer and Parkinson’s disease. Understanding the role of sex will be important in designing interventions and in understanding basic aging mechanisms. Aging also shows sex differences in model organisms. Dietary restriction (DR), reduced insulin/IGF1-like signaling (IIS) and reduced TOR signaling each increase life span preferentially in females, in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 82 publications
4
82
1
1
Order By: Relevance
“…Based on large-scale rodent CR studies in both sexes using multiple hybrid, inbred and recombinant inbred strains showing considerable sex and strain variation in CR-mediated longevity [16,17], it has been proposed that in mice, females respond better to CR [1820] whilst in rats the opposite is true [20]. However, there are many reported exceptions, making these generalizations unhelpful.…”
Section: Sex Differences In Response To Cr In Preclinical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on large-scale rodent CR studies in both sexes using multiple hybrid, inbred and recombinant inbred strains showing considerable sex and strain variation in CR-mediated longevity [16,17], it has been proposed that in mice, females respond better to CR [1820] whilst in rats the opposite is true [20]. However, there are many reported exceptions, making these generalizations unhelpful.…”
Section: Sex Differences In Response To Cr In Preclinical Modelsmentioning
confidence: 99%
“…In the first study, IF initiated in the early phases of autoimmune encephalitis showed protective effects in female mice [47]. However, because only female mice were used in this study, sex-specific responses to DR [21 • ] and/or the etiology and progression of diseases [18] prevent generalization of the finding. In the second study, EOD feeding ameliorated some of the detrimental learning effects and protected against Ab deposition in brains of Alzheimer’s disease (AD) model mice [48].…”
Section: Sex Differences In Response To Timing Of Food Intake In Precmentioning
confidence: 99%
“…A reduction in GH action has also been associated with increased cellular stress resistance and mitochondrial health. However, there are sex-specific differences (90,313,314,315) as well as unavoidable tradeoffs in the process. A reduced stature, obesity and possible reduction in reproductive fitness have been associated with studies in the GH deficient and resistant dwarf mouse models (16,316).…”
Section: Closing Commentsmentioning
confidence: 99%
“…[11,12] In some cases, sex is a much stronger predictor of risk of or protection from disease than DNA variants. [14] Sex differences are also evident in many complex human traits such as lifespan [15] and aging, [16] brain function, [17][18][19][20] circadian rhythms, [21] cardiovascular structure and function [22] and immunological responses, [6,23] among others. [13] In addition, treatment responses and side effects to drugs for many disorders differ between males and females.…”
Section: Sexual Dimorphisms In Human Health and Disease Come To The Forementioning
confidence: 99%
“…[13] In addition, treatment responses and side effects to drugs for many disorders differ between males and females. [14] Sex differences are also evident in many complex human traits such as lifespan [15] and aging, [16] brain function, [17][18][19][20] circadian rhythms, [21] cardiovascular structure and function [22] and immunological responses, [6,23] among others. [24,25] The variety of systems exhibiting sexual dimorphisms implies that exploring these differences will afford valuable insights into disease risk and etiology and will lead to more sex-appropriate treatment options.…”
Section: Sexual Dimorphisms In Human Health and Disease Come To The Forementioning
confidence: 99%